The utilization of pumpkin as a substitution ingredient for making steam cake to improve organoleptic quality and food acceptance - Lamia Diang Mahalia; Teguh Supriyono; Frensia Desi Riska Sari (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2022)
Background: Pumpkin production in Indonesia is quite high but its utilization is still low. Public knowledge related to pumpkin is very simple, starting from how to process it until become a food product. Pumpkin can be processed into various kinds of food like steamed cake. Aim: The aim of this research is to determine the right concentration of pumpkin and wheat flour from the panelist's point of view in an effort to improve the organoleptic quality and acceptability of the pumpkin steam cake.  Methods: This is an experimental research with a completely randomized design. The first stage is making of pumpkin steam cake consist of three concentration variations of pumpkin vs wheat flour. The formulas are P1 (10% : 90%), P2 (20% : 80%) and P3 (30% : 70%). The second stage is to carry out organoleptic and acceptability tests. The data is processed and analyzed descriptively. Results and discussion: Most of panelists was very liked with pumpkin steam cake that using P3 formula compared to the P1 and P2 formulas. The steam cake that produced using the P3 formula has a very yellow color, very distinctive aroma of pumpkin, very sweet taste, and very soft texture. Conclusion: The substitution of pumpkin in the manufacture of steam cake can improve its organoleptic quality and acceptability. This finding is expected to provide information regarding the use of pumpkin as a food product, so it can increasing people's consumption of nutritious food.